Contracting Compliance: A Discussion of the Ethical Implications of Behavioural Contracts in the Rehabilitation Setting - Cooper, Jane; Heesters, Ann; Bianchi, Andria; Rodrigues, Kevin; Brown, Nathalie (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2019)
The pervasive use of contracts in healthcare is a source of unease for many healthcare ethicists and patient advocates. This commentary examines the use of such contracts with individuals in rehabilitation settings who have complex medical and behavioural issues. The goals of this paper are to examine the many factors that can lead to contract use, to discuss some legal and ethical implications of contract use, and to assess contract use in light of concerns about health equity. The paper concludes with some practical alternatives to the use of such contracts, and refers specifically to tools that might be borrowed from the field of behavioural therapy.